Incorporating cultivar-specific stomatal traits into stomatal conductance models improves the estimation of evapotranspiration enhancing greenhouse climate management - Körner, Oliver; Fanourakis, Dimitrios; Chung-Rung Hwang, Michael; Hyldgaard, Benita; Tsaniklidis, Georgios; Nikoloudakis, Nikolaos; Larsen, Dorthe Horn; Ottosen, Carl Otto; Rosenqvist, Eva (My University, 2021)
The effect of considering cultivar differences in stomatal conductance (gs) on relative air humidity (RH)-related energy demand was addressed. We conducted six experiments in order to study the variation in evapotranspiration (ETc) of six pot rose cultivars, investigate the underlying processes and parameterise a gs-based ETc model. Several levels of crop ETc were realised by adjusting the growth environment. The commonly applied Ball–Woodrow–Berry gs-sub-model (BWB-model) in ETc models was validated under greenhouse conditions, and showed a close agreement between simulated and measured ETc. The validated model was incorporated into a greenhouse simulator. A scenario simulation study showed that selecting low-gs cultivars reduces energy demand (≤5.75%), depending on the RH set point. However, the BWB-model showed poor prediction quality at RH lower than 60% and a good fit at higher RH. Therefore, an attempt was made to improve model prediction: the in situ-obtained data were employed to adapt and extend either the BWB-model, or the Liu-extension with substrate water potential (Ψ; BWB-Liu-model). Both models were extended with stomatal density (Ds) or pore area. Although the modified BWB-Liu-model (considering Ds) allowed higher accuracy (R2 = 0.59), as compared to the basic version (R2 = 0.31), the typical lack of Ψ prediction in greenhouse models may be problematic for implementation into real-time climate control. The current study lays the basis for the development of cultivar specific cultivation strategies as well as improving the gs sub-model for dynamic climate conditions under low RH using model-based control systems.
Keywords: Climate control; Relative air humidity; Simulation model; Stomatal conductance; Stomatal density; Transpiration